2021
DOI: 10.1371/journal.pone.0244050
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of COVID-19 related knowledge and preparedness in health professionals at selected health facilities in a resource-limited setting in Addis Ababa, Ethiopia

Abstract: Background The World Health Organization has declared that infection with SARS-CoV-2 is a pandemic. Experiences with SARS in 2003 and SARS-CoV-2 have shown that health professionals are at higher risk of contracting COVID-19. Hence, it has been recommended that aperiodic wide-scale assessment of the knowledge and preparedness of health professionals regarding the current COVID-19 pandemic is critical. Objectives This study aimed to assess the knowledge and preparedness of health professionals regarding COVID… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
1
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(40 citation statements)
references
References 23 publications
1
34
1
4
Order By: Relevance
“…A study from Ethiopia showed that half (50%) of the healthcare providers were not satisfied with the available medical equipment for COVID-19 treatment in their hospitals. 33 A global study that included African countries also reported that over half (53%) of healthcare workers working in maternal and neonatal health service provisions in low/middle-income countries did not receive updated guidelines for the management of COVID-19. 42 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A study from Ethiopia showed that half (50%) of the healthcare providers were not satisfied with the available medical equipment for COVID-19 treatment in their hospitals. 33 A global study that included African countries also reported that over half (53%) of healthcare workers working in maternal and neonatal health service provisions in low/middle-income countries did not receive updated guidelines for the management of COVID-19. 42 …”
Section: Resultsmentioning
confidence: 99%
“…The study from Ethiopia showed that healthcare workers generally had moderate knowledge on detection and management of COVID-19. 33 Another study showed limited understanding of case definition, identification of high-risk patients, tests appropriate to identify suspected cases and lack of adequate preventive measures to minimise transmission. 42 In this study, only 15% of the participants perceived that they had complete knowledge to provide maternity care to patients with COVID-19.…”
Section: Resultsmentioning
confidence: 99%
“…Socio-demographic Issues in adequate implementation of public health measures 21,22,23 ○ Furthermore, Peru is leading some interesting aspects compared to Latin America in the implementation of telemedicine 24,25,26,27 ○…”
Section: Data Collection Instrumentsmentioning
confidence: 99%
“…Inadequacy in such preparedness was represented mainly in scarcity of the equipment and medications [3][4][5] , inadequate staffing, and improper hospitals' infrastructure [5][6][7][8] Another important factor in determining the preparedness of health care systems was nurses' knowledge about COVID-19 case definition and treatment. Unfortunately, many prior studies showed that knowledge deficit, reliance on social media to get information about COVID-19, and inadequate scientific training programs on COVID-19 management, contributed considerably to improper care of clients with COVID-19 disease [3][4][5][6][9][10][11] . Inadequate knowledge about COVID-19 was suggested to be a significant contributor to exaggerated feeling of fear, anxiety, psychological distresses, in addition to low self-confidence and low self-esteem, and therefore complicating the mitigation efforts of COVID-19 aftermath [12] .…”
Section: Introductionmentioning
confidence: 99%